Effect of culture conditions on the whole cell activity of recombinant Escherichia coli expressing periplasmic organophosphorus hydrolase and cytosolic GroEL/ES chaperone - Kim, Kyeoung Rok; Song, Young Hoon; Seo, Jeong Hyun; Kang, Dong Gyun; Kim, Chang Sup (Biotechnology and bioprocess engineering, 2016)
Specific whole cell activity strongly affects sensitivity and detection limit of whole cell-based biosensors. Previously, we developed recombinant Escherichia coli coexpressing periplasmic organophosphorus hydrolase (OPH) and cytosolic chaperone GroEL-GroES (GroEL/ES). In present work, we investigated the effect of culture conditions on whole cell OPH activity. Especially, the whole cell OPH activity was significantly affected by the concentration of tetracycline that is an inducer for chaperone GroEL/ES. When cultured at 20°C for 31 h in M9 medium containing 1 mM IPTG, 50 ng/mL tetracycline, and 500 µM CoCl 2 , the recombinant E. coli exhibited a specific whole cell OPH activity (U/OD 600 ) of ~0.55, which is 2.6-fold higher than that of recombinant E. coli cultured as previously described conditions. In addition, recombinant cells showed adequate storage stability for 1 week with 100% of original response. Finally, the improved activity and adequate stability in the whole cell biocatalyst will contribute to sensitivity, detection time, and stability of a whole cell-based biosensor for the detection of toxic organophosphates.